2016
DOI: 10.1016/j.jveb.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Regional brain activations in awake unrestrained dogs

Abstract: Due to its accessibility, tractability, evolutionary history, and social intelligence, the domestic dog is increasingly used as a model animal in behavioral studies. While this has led to new insights into canine cognition, understanding of dog brain function has not advanced apace. Practical and ethical concerns have limited the use of the invasive brain imaging techniques typically used with primate and rodent models. Now, with the advent of awake, unrestrained canine fMRI (Berns, Brooks & Spivak, 2012), dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…Thus, even though all the dogs were cleared for scanning by reaching performance criterion, they may have used different mechanisms to process the words. Like our previous fMRI studies, heterogeneity seems to be the rule ( Cook et al, 2016a , b ). Even so, the accuracy of the classifier was not correlated with a dog’s performance.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Thus, even though all the dogs were cleared for scanning by reaching performance criterion, they may have used different mechanisms to process the words. Like our previous fMRI studies, heterogeneity seems to be the rule ( Cook et al, 2016a , b ). Even so, the accuracy of the classifier was not correlated with a dog’s performance.…”
Section: Discussionsupporting
confidence: 79%
“…Since 2012, pet dogs have been trained using positive reinforcement to lie still during fMRI scans in order to explore a variety of aspects of canine cognition ( Berns et al, 2012 , 2013 ). These studies have furthered our understanding of the dog’s neural response to expected reward, identified specialized areas in the dog brain for processing faces, observed olfactory responses to human and dog odors, and linked prefrontal function to inhibitory control ( Cook et al, 2014 , 2016a ; Berns et al, 2015 ; Dilks et al, 2015 ; Cuaya et al, 2016 ). In one fMRI study, dogs listened to human and dog vocalizations through headphones and showed differential activation within regions of the temporal and parietal cortex ( Andics et al, 2014 ).…”
Section: Introductionmentioning
confidence: 95%
“…Many other tests could be useful in OA monitoring, including thermal imaging and mechanical nociceptive threshold testing 178,179 . Functional activity monitoring, force plate analysis and advanced MRI are performed on dogs in a manner that mirrors their use in human patients, and brain imaging in conscious pet dogs is also reliable and practical and could potentially be used for comparative neuroscience studies 180,181 .…”
Section: A Means To Identify the Genetic Basis Of Analogous Diseasementioning
confidence: 99%
“…So far, five independent research groups-two in the USA (Atlanta, GA, and Auburn, AL), one in Mexico (Querétaro), and two in Europe (Budapest, Hungary, and Vienna, Austria)-have captured brain images of nonsedated and largely unrestrained dogs, and their work and publications indicate the interest in and the importance of this new frontier in functional neuroimaging (see Andics & Miklósi, 2018;Bunford, Andics, Kis, Miklósi, & Gácsi, 2017;Cook, Brooks, Spivak, & Berns, 2016;Huber & Lamm, 2017;and Thompkins et al, 2016, for reviews). Starting with studies on reward processing (Berns et al, 2012;Berns, Brooks, & Spivak, 2013;Berns, Brooks, Spivak, & Levy, 2017;Cook, Spivak, & Berns, 2014), subsequent studies investigated the default mode network (Kyathanahally et al, 2015), olfactory processing (Berns, Brooks, & Spivak, 2015;Jia et al, 2014;Jia et al, 2015), face processing (Cuaya, Hernández-Pérez, & Concha, 2016;Dilks et al, 2015;Thompkins et al, 2018), response inhibition , auditory processing (human and dog vocalizations: Andics, Gácsi, Faragó, Kis, & Miklósi, 2014;human words: Andics et al, 2016;Prichard, Cook, Spivak, Chhibber, & Berns, 2018), and emotion processing ("jealousy"; ; human emotional faces: Hernández-Pérez, Concha, & Cuaya, 2018).…”
mentioning
confidence: 99%